2021
DOI: 10.3390/catal11040458
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of an Ag3PO4/Nb2O5 Photocatalyst for the Degradation of Dye

Abstract: In this work, the photocatalytic performance of Ag3PO4, Nb2O5 and Ag3PO4/Nb2O5 hybrid photocatalysts to degrade methyl orange dye, MO, in an aqueous solution under visible light irradiation was evaluated. The Ag3PO4 and Ag3PO4/Nb2O5 photocatalysts, with various Ag to Nb molar ratios, were prepared using a facile precipitation method. The photocatalysts were characterized by X-ray diffraction, UV–Visible, X-ray Photoelectron, and Photoluminescence spectroscopies. Upon the addition of Ag3PO4, the band gap energy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…In 2010, Ye et al [11] reported a novel visible light photocatalyst, Ag 3 PO 4 , which showed very strong oxidation capacity and high visible-light catalytic activity. In addition, its quantum efficiency reached 90%, far higher than that of other metal oxide semiconductor photocatalysts [12][13][14][15]. However, Ag 3 PO 4 is prone to photoelectron corrosion and becomes unstable during photocatalytic reaction, which severely limits the application of Ag 3 PO 4 in the field of photocatalysis.…”
Section: Introductionmentioning
confidence: 99%
“…In 2010, Ye et al [11] reported a novel visible light photocatalyst, Ag 3 PO 4 , which showed very strong oxidation capacity and high visible-light catalytic activity. In addition, its quantum efficiency reached 90%, far higher than that of other metal oxide semiconductor photocatalysts [12][13][14][15]. However, Ag 3 PO 4 is prone to photoelectron corrosion and becomes unstable during photocatalytic reaction, which severely limits the application of Ag 3 PO 4 in the field of photocatalysis.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, besides finding solutions to increase specific surface area, researchers also focus on enhancing the structural stability of the materials by adjusting the ratio of Ag + and PO 3− 4 [9,16,17] to find the most stable structure. In addition, increasing the lifetime of the electron/hole pair to increase the photocatalytic efficiency has always been of interest to research through the creation of a heterojunction between APO and other semiconductors [15,[18][19][20][21] as well as doping of APO with suitable ions. [22][23][24] Previous studies showed that the different concentrations of Ag + and PO 3− 4 in the starting solutions significantly affects the particle size and morphology, crystallinity, absorption capability and structure stability of Ag 3 PO 3 .…”
Section: Introductionmentioning
confidence: 99%